Microstructure and strength of diffusion bonded 304 stainless steel/tungsten joints using different interlayers. (May 2021) - Sun, Lixing; Song, Xuhang; Dong, Yuntao; Zou, Juntao; Li, Xiang; Ni, Lei; Gao, Lei; Liang, Shuhua
Abstract: Diffusion bonding was successfully applied to join 304 stainless steel (SS) and tungsten (W) using interlayers of Cu and Ni, and the effect of bonding temperature on microstructure and strength of 304SS/Cu/W and 304SS/Ni/W joints is investigated. The present study shows that a sound 304SS/Cu/W joint with sufficient mutual diffusion across 304SS/Cu and Cu/W interfaces is obtained at a bonding temperature of 1000 ℃, in which solid solutions occur at Cu/W interface. The 304SS/Cu/W joint bonded at 1000 ℃ shows the highest shear strength of 277.2 MPa and good ductility. The occurrence of cracks at 304SS/Cu interface with the increasing of bonding temperature results in the decrease in shear strength of 304SS/Cu/W joints under brittle fracture. The 304SS/Ni/W joints are free of crack in the bonding temperatures of 850 ℃–1000 ℃, which shows the highest shear strength of 237 MPa bonded at 950 ℃ due to occurrence of intermetallic compound Ni4 W in the diffusion layer close to Ni/W interface. No obvious diffusion layer at 304SS/Ni/W is observed following bonding at 850 ℃ and 900 ℃. The micro-voids in the diffusion layer bonded at 1000 ℃ are responsible for the lower shear strength of joint than that of 950 ℃.